Sacred realms in virtual worlds: The making of Buddhist spaces in Second Life. (August 2019) - Falcone, Jessica M
Second Life, a virtual world, has been heralded by some scholars and transhumanists as a sacred, "heavenly" space. Through detailed ethnographic work on Buddhist religious spaces in Second Life, this article argues instead that just as in actual life, virtual life is comprised of both sacred and profane spaces. By demonstrating different types of Buddhist spaces, community-practice-oriented and individual-practice-oriented, and the meaning that these spaces hold for practitioners, readers come to understand that the sacrality in Second Life is just as contingent and constructed as it is in the actual, physical world.